Postintubation Tracheal Rupture – A Case Report - Hasan, Rajib; Islam, Md Motiul; Hamid, Tarikul; Halim, Mohammad Rabiul; Ahmed, Kazi Nuruddin; Rahman, AHM Hafizur; Hassan, Shakera Binte; Hoque, Md Mazharul; Abdul Karim, Faisal Mohammed (Bangladesh Critical Care Journal, 2022)
Iatrogenic tracheal rupture is a rare but recognized complication after endotracheal intubation. Although rare, it carries high morbidity and mortality. Seemingly uneventful intubations can result in injury to the trachea requiring prompt diagnosis and management. Here, we report a patient of post intubation tracheal rupture who was successfully treated by conservative management. Bangladesh Crit Care J September 2022; 10(2): 163-165